コウクウ ジキ ソクリョウ ニ ヨル ショウワ キチ ト ミズホ キチ カン ノ ジキ イジョウ - 渋谷, 和雄; シブヤ, カズオ; 神沼, 克伊; カミヌマ, カツタダ; 伊神, 煇; イカミ, アキラ; 伊藤, 潔; イトウ, キヨシ; Shibuya, Kazuo; Kaminuma, Katsutada; Ikami, Akira; Ito, Kiyoshi (1984)
P(論文) 第21次南極地域観測隊(以下「JARE-21」といい, 他次隊も同様に略称する)は, 昭和基地とみずほ基地を結ぶ輸送ルートに沿って, プロトン全磁力計による航空磁気測量を実施した。測定された全磁力値から, IGRFモデルによる標準磁場の除去と日変化成分の補正を行って, 同ルート上での磁気異常分布を求めた。得られた磁気異常分布に含まれる不確かさは20-30nT程度と思われ, 次の二つの特徴を持つ。一つはS16-S30付近の-250から350nTに及ぶ異常, もう一つはH260からZ50にかけての-270から140nTに及ぶ異常で, 両者とも10-30kmの波長を持っている。JARE-17が同一ルート上で地上全磁力値を測定しているので, その値から計算される磁気異常値と今回得られた磁気異常分布との対応を見た。また, すでに得られているフリーエア重力異常分布との比較検討も行った。 The 21st Japanese Antarctic Research Expedition (JARE-21) made aeromagnetic surveys along the traverse route from Syowa to Mizuho Stations by using a proton precession magnetometer. Reductions of International Geomagnetic Reference Field and diurnal variations were applied to the observed total intensity data, and the geomagnetic anomaly profile along the route was obtained. The uncertainty in the anomaly profile is considered to be 20-30nT. There is a characteristic anomaly around S16-S30 which ranges from -250 to 350nT. There is also another anomaly from H260 to Z50,which ranges from -270 to 140nT. Both anomalies have the wave-length of 10-30km. The correspondence of the ground data by JARE-17 with the obtained anomaly profile is rather good. The comparison of the geomagnetic anomaly profile with the previously obtained free-air gravity anomaly profile was made. departmental bulletin paper